Reduction of Hip Arthroscopy Post-Operative Pain Using Ultrasound-guided Fascia-Iliaca Block: A Prospective Randomized Control Trial. Issue 7 (30th July 2018) - Glomset, John Larson; Kim, Eugene J.; Tokish, John M.; Renfro, Suzanne D.; Seckel, Tyler B.; Adams, Kyle J.; Folk, Jason
Objectives: Ultrasound guided fascia-Iliaca blocks have been used for pain control following hip arthroscopy. There is little evidence regarding their effectiveness in comparison to other pain control modalities in hip arthroscopy patients. Purpose: : To compare efficacy of ultrasound guided fascia iliac block with intra-articular ropivacaine in controlling pain after hip arthroscopy. Methods: Between 2015 and 2017, 95 patients undergoing hip arthroscopy were randomly assigned to 2 groups. The first group received an ultrasound-guided fascia-iliaca block with 50-60mLs of 0.35% ropivacaine. The second group received intra-articular injection of 20 mL of 0.5% ropivacaine at the completion of the surgical case. Primary outcomes were post-operative pain scores in the recovery room, at PACU discharge, at 2 weeks, 6 weeks, and 3 months. Secondary outcomes included intraoperative and PACU narcotic usage (converted to morphine equivalent use) as well as readmission rates, PACU recovery time and postoperative nausea and vomiting (PONV). Results: Postoperative pain across all points did not significantly differ between the 2 groups. Intraoperative and PACU narcotics did not differ significantly between the 2 groups. Readmission rates, PACU recovery time and PONV did not significantly differ between the 2 groups. There were no associated complications in either group. Conclusion: Ultrasound guided fascia iliaca block for hip arthroscopy had no clinical advantage when compared to one time intra-articular ropivacaine injection. Furthermore, an intraarticular injection decreases costs and is a safe and more efficient modality for postoperative pain control following hip arthroscopy.